Comparative Therapeutic Efficacy of 153Sm-EDTMP and 177Lu-EDTMP for Bone Pain Palliation in Patients with Skeletal Metastases: Patients’ Pain Score Analysis and Personalized Dosimetry - Sharma, Sarika; Singh, Baljinder; Koul, Ashwani; Mittal, Bhagwant Rai (Frontiers in Medicine, 2017)
Introduction The aim of the present study was to compare the therapeutic efficacy of 153Sm-EDTMP and 177Lu-EDTMP in pain palliation in cancer patients with skeletal metastases. Materials and methods Thirty patients (25 M:5 F, mean age: 66.0 ± 14.7 years) of breast/prostate cancer with documented skeletal metastases were recruited prospectively. Twenty patients were considered randomly for treatment with 153Sm-EDTMP and with 177Lu-EDTMP in 10 patients, respectively. Using fixed dose of 37.0 MBq/kg body weight of each, the mean administered doses of 153Sm-EDTMP and 177Lu-EDTMP were 2,155.2 ± 419.6 MBq (1,347–2,857) and 1,935.1 ± 559.4 MBq (1,073–2,627), respectively. Anterior and posterior whole body images were acquired at different time points following radioactivity administration. The first data set of pre-void images (acquired at 0.5 h) representing the total activity of either of 153Sm-EDTMP or 177Lu-EDTMP was considered as reference images. All the serial images were used for patients’ dosimetry analysis by using organ level internal dosimetry assessment algorithm. Reduction in pain scoring was assessed clinically over 8 weeks by using appropriate WHO criteria and correlated with the absorbed dose to the metastatic sites. Results A total of 86 metastatic lesions clearly visualized on post-therapy serial images (matching on bone scans) were evaluated for absorbed dose calculations. Both 153Sm-EDTMP and 177Lu-EDTMP delivered similar absorbed dose to the metastatic sites, i.e., 6.22 ± 4.21 and 6.92 ± 3.92 mSv/MBq, respectively. The mean absorbed doses to various other organs were found to be comparable and within the safe limits. A complete response (CR) for each radionuclide was evaluated as 80.0%. No significant alternation in blood parameters and no untoward reaction were observed. However, a mild to severe toxicity was observed in two patients (1 each with 153Sm-EDTMP and 177Lu-EDTMP). Kaplan–Meier survival analysis demonstrated that 27/30 patients had pain-free survival (CR) up to the observational period of 8 weeks. However, no statistically significant correlation could be established between the pain scoring and absorbed dose to metastatic sites. Conclusion Both the radionuclides thus offer an effective and comparable therapeutic efficacy for bone pain palliation at an affordable cost and can be used interchangeably as per the availability.